Increasing access to modern contraceptives: the potential role of community solidarity through altruistic contributions - Onwujekwe Obinna E; Ogbonna Chinwe; Uguru Nkoli; Uzochukwu Benjamin SC; Lawson Agathe; Ndyanabangi Bannet (BMC, 2012)
Abstract Background There is an urgent need for universal access to modern contraceptives in Nigeria, to facilitate the achievement of the Millennium Development Goals and other national goals. This study provides information on the potential role of community solidarity in increasing access to contraceptives for the most-poor people through exploration of the role of altruism by determining level of altruistic willingness to pay (WTP) for modern contraceptives across different geographic contexts in Nigeria. Methods It was a cross-sectional national survey which took place in six states spread across the six-geopolitical zones of the country. In each state, an urban and a rural area were selected for the study, giving a total of 6 urban and 6 rural sites. A pre-tested interviewer-administered questionnaire was used to collect information from at least 720 randomly selected householders from each state. The targeted respondent in a household was a female primary care giver of child bearing age (usually the wives), or in her absence, another female household member of child bearing age. A scenario on altruistic WTP was presented before the value was elicited using a binary with open-ended follow-up question format. Test of validity of elicited altruistic WTP was undertaken using Tobit regression. Findings More than 50 % of the respondents across all the states were willing to contribute some money so that the very poor would be provided with modern contraceptives. The average amount of money that people were willing to contribute annually was 650 Naira (US$4.5). Mean altruistic WTP differed across SES quintiles and urban-rural divide (p < .01). Multiple regression analysis showed that age was negatively related to altruistic WTP (p < 0.05). However, years of schooling, being employed by government or being a big business person, prior experience of paying for contraceptives and socioeconomic status had statistically significant effects on altruistic WTP (p < 0.05). Conclusion There is room for community solidarity to ensure that the very poor benefit from modern contraceptives and assure universal coverage with modern contraceptives. The factors that determine altruistic WTP should be harnessed to ensure that altruistic contributions are actually made. The challenge will be how to collect and pool the altruistic contributions for purchasing and delivering modern contraceptives to the most-poor, within the context of community financing.